Proceedings of the 2016 4th International Conference on Machinery, Materials and Information Technology Applications 2016
DOI: 10.2991/icmmita-16.2016.159
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Navigation System of Hexapod Robot based on Fuzzy Neural Network

Abstract: A closed-loop autonomous navigation system based on fuzzy neural network is proposed to deal with the autonomous navigation issue of hexapod robot in unknown environment. The closed-loop system is designed in order to optimize the output performance. The navigation algorithm is designed to combine fuzzy control with neural network. Fuzzy control is used to realize the ability of logical reasoning and neural network is conducive to learning and training ability. The ambient sensors are a GPS sensor, an electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In this paper, the tactile force-feedback system is developed and installed on the foot ends of the hexapod robot. The structure of the hexapod robot (Li et al, 2016) is shown in Figure 2(a). Its leg structure includes the arm steering gear, leg steering gear, foot steering gear, and foot end.…”
Section: Dgftra-pnn Under Multiple Gaits Of Hexapod Robotsmentioning
confidence: 99%
“…In this paper, the tactile force-feedback system is developed and installed on the foot ends of the hexapod robot. The structure of the hexapod robot (Li et al, 2016) is shown in Figure 2(a). Its leg structure includes the arm steering gear, leg steering gear, foot steering gear, and foot end.…”
Section: Dgftra-pnn Under Multiple Gaits Of Hexapod Robotsmentioning
confidence: 99%